ANALYSIS OF PRICE AND QUALITY OF CUSTOMER LOYALTY IN TRANSPORT SERVICES DAMRI AMONG DISTRICTS IN WEST KALIMANTAN - B31109036, Tengku Arfandi (Jurnal Manajemen Update, 2015)
Good or bad quality of service will impact the image of the company itself, and which will influence the consumer's decision to use transportation services Damri. Therefore, the company should be able to provide products or services at competitive rates, facilities and better service quality than competitors-competitors in order to attract consumers. If the customer is not satisfied, then it will leave the company that will lead to a decline in sales and profits will decrease even further losses for the company. Writing method in this paper is a survey method and tool is the method of quantitative analysis. The study concluded the following: 1) There is no significant price effect on customer loyalty. It can be seen from the value of t count> t table 2.066> 2.000) and significance value> significance level (Î±) of 0.05 (0.04 <0.05). 2) There is no significant influence on customer loyalty reliability. It can be seen from the t value <t table (-1.458 <2.000) and a significance value> significance level (Î±) of 0.05 (0.148> 0.05), 3) There is no significant influence responsiveness to customer loyalty. It can be seen from the t value <t table (0.108 <2.000) and a significance value> significance level (Î±) of 0.05 (0.914> 0.05), 4) There is no significant influence on customer loyalty guarantee. It can be seen from the t value <t table (-0.078 <2.000) and a significance value> significance level (Î±) of 0.05 (0.940> 0.05), 5) There is no significant influence on customer loyalty empathy. It can be seen from the t value <t table (1.639 <2.000) and a significance value> significance level (Î±) of 0.05 (0.105> 0.05) and 6) There is a significant influence on customer loyalty keberwujudan. It can be seen from the value of t count> t table (11.178> 2.000) and significance value <significance level (Î±) of 0.05 (0.000> 0.05). Â  Keywords: Price, Quality Service, Customer Loyalty